2019
DOI: 10.3233/jad-190328
|View full text |Cite
|
Sign up to set email alerts
|

Regular Exercise Enhances Cognitive Function and Intracephalic GLUT Expression in Alzheimer’s Disease Model Mice

Abstract: Brain energy metabolic impairment is one of the main features of Alzheimer's disease (AD) and is considered an underlying factor involved in cognitive impairment. Therefore, brain energy metabolism may represent a new therapeutic target for AD medical interventions. Among nutrients providing energy, glucose, the primary energy source, cannot cross the blood-brain barrier freely without specific glucose transporters (GLUTs), which are essential for the maintenance of cerebral energy metabolism homeostasis. Seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 52 publications
2
24
0
Order By: Relevance
“…For instance, 6-month-old APP/PS1 mice subjected to regular exercise during 4 weeks exhibited improved learning and spatial memory together with decreased levels of Aβ and p-Tau in the cortex and hippocampus. Additionally, it promoted enhanced mitochondrial function and increased synaptic density (Pang et al, 2019). Likewise, it was recently reported that hippocampus-dependent memory and synaptic puncta were positively modulated in 12-month-old mice of the same strain subjected to running during 4 months (Zhang et al, 2020).…”
Section: Physical Activity (Pa)mentioning
confidence: 78%
“…For instance, 6-month-old APP/PS1 mice subjected to regular exercise during 4 weeks exhibited improved learning and spatial memory together with decreased levels of Aβ and p-Tau in the cortex and hippocampus. Additionally, it promoted enhanced mitochondrial function and increased synaptic density (Pang et al, 2019). Likewise, it was recently reported that hippocampus-dependent memory and synaptic puncta were positively modulated in 12-month-old mice of the same strain subjected to running during 4 months (Zhang et al, 2020).…”
Section: Physical Activity (Pa)mentioning
confidence: 78%
“…An animal study has revealed that regular exercise decreases the expression of Aβ and phosphorylated tau production, with increased production of ATP in the brain. Researchers have found an increased number of synapses and improved expression levels of Glut1 and Glut3 expression in the central nervous system in a mouse model of AD [ 163 ].…”
Section: Brain Glucose Transporters As Targets For Alzheimer’s Diseasementioning
confidence: 99%
“…In mice, acute aerobic exercise (voluntary wheel running) led to an increase in expression of GLUT1 in the brain (Allen & Messier, 2013). Similarly, regular exercise in mice increased expression of GLUT1 in cardiomyocytes (Jiang et al, 2020) and the central nervous system (Pang et al, 2019). In addition, upregulation of GLUT1 in the cortex was reported after a single bout of aerobic exercise in rats (Takimoto & Hamada, 2014).…”
Section: Potential Mechanisms Underlying the Benefit Of Exercisementioning
confidence: 98%